Stability analysis for a milling system considering multi-point-contact cross-axis mode coupling and cutter run-out effects. (July 2020) - Jiang, Shanglei; Sun, Yuwen
Highlights: A milling dynamic model with cross-axis mode coupling effect is established. A novel strategy is proposed for exactly identifying system's dynamic parameters. The model can significantly improve the prediction accuracy of stability limits. The model is verified by a series of down and up milling experiments. Abstract: Stability analysis is essential for milling operations to enable high machining productivities without sacrificing surface quality and introducing significant surface errors. Its exact implementation depends on the dynamics modeling with reliable requirement of system's dynamic parameters. However, existing modal testing strategies neglect the cross-axis mode coupling effect along the multi-point-contact zone between the tool and workpiece. This leads to some losses of accuracy for the dynamic parameters and further makes the dynamic model fail to reflect the real tool-workpiece interaction mechanism. Aiming at improving the model accuracy, a novel modal testing strategy is proposed, which takes both the cross-axis and cross-point mode coupling effects into account in identifying the dynamic parameters. Meanwhile, new parameter identification technique is theoretically given when processing measured direct, cross-axis and cross-point frequency response functions. And matrix assembly technique is also presented for matching the identified dynamic parameters to the system dynamic equation. On the other hand, instead of single-point-contact dynamics assumed at the tool tip, a dynamic model with multi-point-contact dynamics is developed for a common multi-delay milling system, where run-out effect is included for calculating multiple regenerative dynamic cutting forces. The resulting multi-delay system dynamic equation is then solved by an improved semi-discretization method. To validate the developed model with the dynamic parameters obtained by the proposed modal testing strategy, down and up milling experiments are carried out, and two cutters with different diameter are employed in the experiments. The results show that the proposed approach significantly improves the stability prediction accuracy of a milling system especially involving a big axial depth of cut.